Barriers impeding research data sharing on chronic disease prevention among the older adults in low-and middle-income countries: a systematic review - Neema Florence Vincent Mosha; Patrick Ngulube (Frontiers in Public Health)
IntroductionChronic diseases, including cardiovascular disease, diabetes, cancer, and chronic respiratory diseases, are a growing public health concern in low-and middle-income countries (LMICs) among the older population. The current review aimed to identify the main barriers that impede researchers from sharing research data on the prevention of chronic diseases in older adults living in LMICs). The review included both older women and men from these countries.MethodsStudies were selected from 11 databases, including Web of Science, Scopus, PubMed, Taylor and Francis, Biomedical Central, BioOne, CINAHL, EBSCOHost, ScienceDirect, Wiley Online, and Google Scholar, were then transferred to CADIMA, an online tool for screening purposes, and a total of 1,305,316 studies were identified through a robust search strategy. CADIMA also ensured the quality of all studies in this review. The sampling techniques were performed by selecting and screening studies per this review’s eligibility criteria. Ultimately, 13 studies were found to meet these criteria. A PRISMA flow chart was used to map out the number of studies that were identified, included, and excluded.ResultsFive main barriers were consistently highlighted, including a lack of necessary resources (9, 69%), dealing with complex and sensitive research data (2,15%), lack of policies, procedures, guidelines (5,38%), medical big data processing and integration (2,15%), and inadequate ethical considerations, legal compliance, and privacy protection (6,46%). Discussion: By shedding light on these obstacles, researchers can develop strategies to overcome the identified barriers and address areas requiring further investigation. The registration details of this review can be found under PROSPERO 2023 CRD42023437385, underscoring the importance of this review in advancing our collective understanding of chronic disease prevention among older adults worldwide.Systematic review registrationPROSPERO, identifier CRD42023437385, available at: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023437385.